(untitled) (Journal of the College of Basic Education, 2024)
The countries of the Islamic Levant played a decisive role in the development of the political policy from which some conquests began after the Islamic conquest of the Levant. The city of Rawand was part of the city of Kashan and was administratively subordinated to Isfahan, and it became one of the important cities that took its role in developing in the political scene after the state of chaos and turmoil arising in The Islamic Levant regions, especially in the regional areas of the mountains extending in Isfahan and Qashan, Rwanda, where this region began the safe embrace of the establishment of the Abbasid state through the efforts of the French and after the weakening of the burden and many countries and Emirates that began to control the political affairs of the Islamic Levant